Effect of hydrogen peroxide on protein degradation of feather meal - C.A. Löest; C.M. Coetzer; Evan C. Titgemeyer; James S. Drouillard (Kansas Agricultural Experiment Station Research Reports, 2002)
Protein degradation of feather meal treated with hydrogen peroxide was evaluated using the in situ bag technique. Bags containing untreated feather meal or feather meal treated with 1.4, 2.5, 2.7, 5.0, or 7.0% hydrogen peroxide (g/100 g feather meal, as fed basis) at various pH and times of heating (55oC) were suspended in the rumen of a cannulated steer for 12 hours. Protein degradabilities of feather meal treated with 2.5 and 2.7% peroxide were only 12 to 19% greater than untreated feather meal, but feather meal treated with 5% peroxide had protein degradabilities 56 to 67% greater than untreated feather meal. Treatment of feather meal with 7% peroxide did not increase protein degradation further. Altering pH and heating (55oC) peroxide-treated feather meal for 30 or 120 minutes had only minor effects on protein degradability.
Keywords: Cattlemen' s Day; 2002; Kansas Agricultural Experiment Station contribution; no. 02-318-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 890; Beef; Hydrogen peroxide; Protein degradation; Feather meal